(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Cibo e religione (e mercato) - 2. L’evoluzione storica del rapporto tra cibo e religione - 3. Elementi utili per una definizione giuridica di macellazione rituale - 4. La questione dello stordimento - 5. La sentenza della Grande Chambre della Corte di giustizia del 29 maggio 2018 (causa C-426/16): la posizione dell’Avvocato Generale Nils Wahl - 6. La sentenza della Grande Chambre della Corte di giustizia del 26 febbraio 2019 (causa C-497/17) - 7. Alcune considerazioni (non) conclusive. Multicultural societies and protection of food identity: some reflections on ritual slaughter. ABSTRACT: The intensification of migratory flows and the demographic increase of the population of the Islamic religion in Europe now make it unavoidable to consolidate that process of cultural integration between different ethnic, linguistic and religious components, which had already begun a few decades ago in Western countries and aimed at defining of a new model of open and pluralist society. This process calls into question, in various areas - including that of food protection - the values ​​of dignity, freedom and equality on which European democracies are founded, imposing the search for new balances between potentially conflicting interests. This contribution aims to investigate the compatibility profiles between respect for the food identity of religious minorities, the protection of human health and food safety and the prohibition of causing unnecessary suffering to animals, to highlight whether the principle of neutrality accepted by the current EU legislation is indeed the most suitable for promoting the fundamental values ​​of European society.